Level raising for p-adic Hilbert modular forms - Newton, J (Institut de Mathématiques de Bordeaux, 2017)
This paper generalises previous work of the author to the setting of overconvergent p-adic automorphic forms for a definite quaternion algebra over a totally real field. We prove results which are analogues of classical ‘level raising’ results in the theory of mod p modular forms. Roughly speaking, we show that an overconvergent eigenform of finite slope whose associated local Galois representation at some auxiliary prime ł - p is (a twist of) a direct sum of trivial and cyclotomic characters lies in a family of eigenforms whose local Galois representation at l is generically (a twist of) a ramified extension of trivial by cyclotomic. We give some explicit examples of p-adic automorphic forms to which our results apply, and give a general family of examples whose existence would follow from counterexamples to the Leopoldt conjecture for totally real fields. These results also play a technical role in other work of the author on the problem of local–global compatibility at Steinberg places for Hilbert modular forms of partial weight one.